Hubungan Sanitasi Lingkungan Dengan Kejadian Diare Di Pulau Balang Lompo Kecamatan Liukang Tupabbiring Kabupaten Pangkep - Munawwarah; Hidayat; Mansur Sididi (Window of Public Health Journal, 2026)
Diarrhea is a condition of having three or more loose stools a day, which is the main cause of death in infants and adults in Indonesia. Poor sanitation conditions, such as improper waste and sewage management and contaminated water sources, are the main risk factors for the transmission of this disease in coastal areas. This study aims to analyze the relationship between environmental sanitation, which includes the provision of clean water, ownership of healthy latrines, and wastewater management, with the incidence of diarrhea on Balang Lompo Island, Pangkep Regency. This study used a quantitative, cross-sectional design. The study population comprised all 915 heads of families (KK) on Balang Lompo Island, selected using a simple random sampling technique. Data were obtained using a questionnaire. The analysis methods used were univariate and bivariate, with the chi-square test. The results of the study showed that there was no relationship between environmental sanitation of clean water supply and the incidence of diarrhea (p-value = 0.690> 0.05%), there was a significant relationship between environmental sanitation of healthy toilet ownership and the incidence of diarrhea (p-value = 0.001<0.05%) and there was a relationship between environmental sanitation of liquid waste management and the incidence of diarrhea (p-value = 0.001<0.05%) The suggestion in this study is that the people of Balang Lompo Island, Pangkep Regency, are expected to pay attention to and maintain environmental sanitation appropriately and meet the requirements in accordance with applicable health standards.